Simulations of Vertical Water Vapor Transport for TC Ingrid (2013). Issue 15 (3rd August 2018) - Allison, Thomas; Fuelberg, Henry; Heath, Nicholas
Abstract: Vertical water vapor transport is examined for tropical cyclone (TC) Ingrid (2013), a Category 1 storm in the Gulf of Mexico that contained deep convection, including numerous overshooting tops. The study employs high‐resolution numerical simulations using the Weather Research and Forecasting model with a smallest grid spacing of 1.33 km and a model top of 10 hPa (~31 km) that extends into the lower stratosphere. Area‐averaged values of vertical motion, water vapor content, its temporal change, and vertical water vapor transport are presented for Ingrid as a whole and for individual regions of the storm. Results show that area‐averaged hydration in the layer ~1–14.5 km between the start and end of the simulation (4.75 days) is due to upward convective transport. Observed overshooting convection is simulated, revealing intense vertical motions that transport large quantities of vapor and ice to the lower stratosphere. Greatest dehydration occurs in the upper troposphere and lower stratosphere between 14.5 and 17.5 km. This layer is found to be supersaturated with respect to ice. This apparently caused water vapor to deposit on the convectively lofted ice, allowing it to then grow and sediment out of the layer, thus producing dehydration. Conversely, hydration occurred between 17.5 and 21 km due in part to that layer being subsaturated with respect to ice. Overall, the study highlights the important role TCs and their embedded overshooting convection play in transporting water vapor to the upper troposphere and lower stratosphere. Key Points: Simulated tropical cyclone Ingrid (2013) had a major influence on the water vapor content of its environment Hydration in the troposphere is related to upward convective transport, including overshooting storms whose tops extend into the stratosphere Hydration and dehydration in the lower stratosphere appear related to ice crystal processes that are poorly resolved in the simulation